AMOBILISASI ENZIM PENISILIN ASILASE SEL TRANSFORMAN ESCHERICHIA COLI SC 50 MENGGUNAKAN GEL POLIAKRILAMIDA - S. Pudjiraharti; M. Wirahadikusumah (Research Center for Chemistry - LIPI, 1994)
Results of study on the immobilization of dialysed fraction of penicillin acylase using various concentrations of acrylamide at BIS concentration 0,8 % are described. The study is an effort to increase the stability and efficiency of the enzyme use. The highest specific activity of the immobilized enzyme (1.38 U/mg protein) was found on immobilization using acrylamide 12.5 %. The penicillin acylase used in this study was obtained from the extraction of Escherichia coli Sc 50 cells. The optimum conditions of catalytic reaction of the enzyme were found 65°C and pH 7.00 both for immobilized and free enzymes. Theoptimum catalytic time was 230 minutes for the immobilized enzyme and 100 minutes for the free one. The immobilized enzyme was found more stable against pH, temperature changes, and storage at the experimental conditions and could be used five times repeatedly with remaining activity of 50 %. The Km value of free enzyme was 7.21 mM and the Vmax was 0.065 unol 6APA/mg protein/minute. Immobilization increased the Km value to 20.26 mM, and decreased Vmax to 0,033 unol 6-APA/mg protein/ minute. Phenylacetic acid was found to be a mixed inhibitor for penicillin acylase E. coli Sc 50 with the inhibition constants of Ki 720.31 mM and Ki' 504.31 mM. Immobilization decreased Ki to 176.58 mM and Ki' to 27.61 mM.